False Balance in Public Health Reporting? Michele Bachmann, the HPV Vaccine, and "Mental Retardation". Issue 2 (1st February 2017) - Thomas, Ryan J.; Tandoc, Edson C.; Hinnant, Amanda
ABSTRACT: This content analysis of media coverage of Michele Bachmann's erroneous comments that the HPV vaccine causes mental retardation explores the relationship between truth-telling (the presentation of accurate information) and balance (presenting opposing perspectives of an issue equally and legitimately) in public health reporting. Of 200 articles analyzed, about 50% provided correction and about 40% provided a counterpoint. We also found that health reporters tended to engage in truth-telling and balance more than political reporters. Implications for theory and practice are discussed.